MOTIVASI ANGGOTA UNIT KEGIATAN MAHASISWA (UKM) KOPERASI MAHASISWA UNIVERSITAS RIAU - Yuli Septiani; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at the Student Activity Unit (UKM) of the Student Cooperative at the University of Riau, which aims to find out about the motivation of members of the student Activity Unit (UKM) Riau University Student Cooperative, and to determine the activeness of student in the membership of the Student Activity Unit (UKM) of the Riau University Student Cooperative. Where student motivation here is seen from three aspects, namely the need for achievement, the need for power and the need for affiliation or membership, while membership activeness is seen from five aspects, namely meetings, payment of savings, attending aducation, events and business. To get the right research results, the writer uses descriptive quantitative method which is presented in tabular form and explained in detail with a total sample of 66 respondents. The results of this study indicate that the motivation of the student Activity Unit (UKM) Student Cooperative is high with a percentage of 81,8% and there is a low relationship between the level of activeness in membership and the level of motivation. For this reason, it is necessary to have a movement to foster member motivation, so that the members high motivation does not fade in the middle of the trip and the motivation that continues to be fostered will make members more active in membership. Key words: Motivation, Member, University of Riau Student Cooperative